2018
DOI: 10.1039/c8nr00885j
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductivity at the lanthanum cuprate/lanthanum–strontium nickelate interface

Abstract: The utilization of interface effects in epitaxial systems at the nanoscale has emerged as a very powerful approach for engineering functional properties of oxides. Here we present a novel structure fabricated by a state-of-the-art oxide molecular beam epitaxy method and consisting of lanthanum cuprate and strontium (Sr)-doped lanthanum nickelate, in which interfacial high-temperature superconductivity (Tc up to 40 K) occurs at the contact between the two phases. In such a system, we are able to tune the superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…In particular, although the LCO (bottom)-LSNO (top) interface is found to be sharp, an obvious Sr redistribution in the LCO phase in growth direction is detected, which slightly changes depending on the doping level in the LSNO layer. The details are discussed in Ref [112]. Lastly, the broad resistance transition to the superconducting state at such high-onset temperature (similar to optimum-doped LSCO) and the reduced Meissner effect should also be pointed out, since this is an indirect evidence of the inhomogeneous superconducting interface with nanoscale superconducting puddles as a consequence of the interface intermixing.…”
Section: Hetero-epitaxy Of La 2 Cuomentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, although the LCO (bottom)-LSNO (top) interface is found to be sharp, an obvious Sr redistribution in the LCO phase in growth direction is detected, which slightly changes depending on the doping level in the LSNO layer. The details are discussed in Ref [112]. Lastly, the broad resistance transition to the superconducting state at such high-onset temperature (similar to optimum-doped LSCO) and the reduced Meissner effect should also be pointed out, since this is an indirect evidence of the inhomogeneous superconducting interface with nanoscale superconducting puddles as a consequence of the interface intermixing.…”
Section: Hetero-epitaxy Of La 2 Cuomentioning
confidence: 96%
“…One recent example of hetero-interface engineering by oxide MBE is the HT-IS with a critical temperature up to T c ≈ 40 K at LCO-La 2−x Sr x NiO 4 (LSNO) multilayers (Fig. 6a) [112]. Note that LCO and LSNO compounds share the same Ruddlesden-Popper 214-crystal structure, and the electronic phase transformation can be achieved by hole-carriers doping by the substitution of the La site with a Sr dopant.…”
Section: Hetero-epitaxy Of La 2 Cuomentioning
confidence: 99%
“…due to concentration of vacancies, defect segregation, cationic and anionic inter-diffusion, Figure 3c). [70,92,125,126] As a consequence, a local redistribution of all the mobile (ionic and electronic) defects is expected in conditions of thermodynamic equilibrium (i.e. constancy of the electrochemical potential for each defect specie) within the so-called space-charge region across the interface, as described by Poisson-Boltzmann equation: [11]…”
Section: Space Chargementioning
confidence: 99%
“…The effect of interface on superconductivity has received much attention. It was demonstrated that superconductivity can occur at the interface of two nonsuperconducting materials [1][2][3][4][5][6], and the critical temperature (T c ) can even be significantly enhanced com-pared with the corresponding single-phase samples [1,[7][8][9]. One of the most intriguing interfaces is the bilayer of La 2 CuO 4 and La 2−x Sr x CuO 4 [LSCO(x)] films.…”
Section: Introductionmentioning
confidence: 99%
“…The lacking of relevant studies might be in part because the heavily Sr-riched LSCO(x) films are not stable due to oxygen vacancies [13,16]. In previous studies [1,[5][6][7]11] of interface superconductivity, the bilayers were grown in a unique atomic-layer-by-layer molecular beam epitaxy (MBE) system that was fantastic in making atomically flat high-quality samples, but might not be suitable in making the heavily Sr-riched LSCO(x) films. In contrast, due to its thermodynamically nonequilibrium nature, pulsed laser deposition (PLD) can be used to produce metastable films far from chemical equilibrium [17].…”
Section: Introductionmentioning
confidence: 99%